Design of Communicative Arabic Listening Skill Assessment to Measure the Language Skills of Islamic Junior High School Students - Andini, Andini; Efriyanto, Aswin Aan; Baroroh, R. Umi; Aufa, Adila Umniati; Rafif, Muhammad Zaqhlul (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to develop a comprehensive Arabic Listening Skill assessment instrument based on a communicative approach tailored for seventh-grade students at MTsN 3 Bogor. The research employs a structured Research and Development (R&D) methodology utilizing the ADDIE instructional design model, specifically limited to the Analyze, Design, and Develop stages. Primary data were obtained directly from subject-matter and evaluation experts, while secondary data were gathered from curriculum documents, syllabi, and relevant literature. Data collection techniques involved observation, interviews, validation questionnaires, and documentation. Furthermore, the collected data were analyzed using both qualitative descriptive analysis to interpret expert feedback and suggestions, and quantitative descriptive analysis to determine the validity and practicality of the developed assessment instrument. The findings indicate the successful development of a communicative Arabic Listening Skill assessment instrument comprising 10 items. These items are formulated through five alternative techniques: Oral Question-and-Answer, Role Play, Oral Retelling, Information Gap, and Task-Based Listening. Furthermore, the developed instrument demonstrated strong theoretical validity, confirming its effectiveness and relevance as a tool for measuring students' authentic Arabic listening proficiency in real-life communication contexts.